Constructing Masculinity in Men’s Skincare Advertising: A Semiotic Study Utilizing Roland Barthes’ Theory - Rahmawati, Nurul (Az-Zahra: Journal of Gender and Family Studies, 2024)
Semiotic is a sign system that reflects various assumptions of a particular society at a certain time. One of the assumptions often heard is the assumption about gender, which can be reflected on media such as advertisements. Thus, this research aims to identify the denotative and connotative signs of linguistic and visual elements in several men’s skincare (NIVEA Men, Pond's Men, Garnier Men, and Vaseline Men) advertisements, and analyze the myth of masculinity portrayed in these advertisements. The method used to analyze this research is a qualitative method, which refers to content analysis. The findings reveal several characteristics of masculinity based on the denotative and connotative meaning of the advertisements' narration. Men are portrayed as intellectual, possessing leadership abilities, embracing challenges, and displaying strength and adventure. The myth of masculinity is further represented through visual elements such as actors, settings, properties, and color saturation. Here, the myth of masculinity reflected men’s affinity for sport, their leadership qualities, ambition, emphasizing their strength, has muscular bodies, beards, mustaches, and along with the depiction of outdoor activities. Overall, the combination of narration and visual elements effectively reflects the concept of masculinity.